Descriptive Analysis Regarding Optic Canal Variations: A Study In South Punjab Region Of Pakistan - Ponum Mirani; Ammara Rasheed; Gul Afshan; Nida Rasheed (Journal of Rawalpindi Medical College)
Objective: This study aimed to conduct a comprehensive investigation into optic canal variations within the South Punjab region of Pakistan. The primary objectives were to analyze the size, shape, and anomalies of the optic canal, providing valuable insights for healthcare professionals and researchers involved in ophthalmology, neurosurgery, and radiology.